IOX1 Fails to Reduce α-Globin and Mediates γ-Globin Silencing in Adult β0-Thalassemia/Hemoglobin E Erythroid Progenitor Cells - Khamphikham P. (2023)
The accumulation of unbound α-globin chains in red blood cells is a crucial pathophysiology of β-thalassemia. IOX1 (5-carboxy-8-hydroxyquinoline) is a broad-spectrum 2-oxoglutarate (2OG)-dependent oxygenase inhibitor that can reduce α-globin mRNA expression in human cord blood erythroid progenitor cells. Therefore, IOX1 has been proposed as a potential compound for β-thalassemia treatment through the decrease in α-globin chain synthesis. However, there is no empirical evidence regarding the consequences of IOX1 in β-thalassemia. In this study, the therapeutic effects of IOX1 were investigated in β0-thalassemia/hemoglobin E (HbE) erythroid progenitor cells during in vitro erythropoiesis. The results indicated that IOX1 had no impact on α-globin gene expression, but it led instead to significant decreases in γ-globin and fetal hemoglobin (HbF, α2γ2) production without affecting well-known globin regulators: KLF1, BCL11A, LRF, and GATA1. In addition, differential mRNA expression of several genes in the hypoxia response pathway revealed the induction of EGLN1, the PHD2-encoding gene, as a result of IOX1 treatment. These findings suggested that IOX1 fails to lower α-globin gene expression; on the contrary, it mediates γ-globin and HbF silencing in β0-thalassemia/HbE erythroid progenitor cells. Because of the negative correlation of EGLN1 and γ-globin gene expression after IOX1 treatment, repurposing IOX1 to study the hypoxia response pathway and γ-globin regulation may provide beneficial information for β-thalassemia.